2017
DOI: 10.1136/heartjnl-2016-310462
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and risk of ischaemic heart disease

Abstract: ObjectiveTo prospectively examine the association between tea consumption and the risk of ischaemic heart disease (IHD).MethodsProspective study using the China Kadoorie Biobank; participants from 10 areas across China were enrolled during 2004–2008 and followed up until 31 December 2013. After excluding participants with cancer, heart disease and stroke at baseline, the present study included 199 293 men and 288 082 women aged 30–79 years at baseline. Information on IHD incidence was collected through disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
(43 reference statements)
1
26
0
Order By: Relevance
“…Tea consumption has been shown to be useful for the prevention of many debilitating human diseases. Several published studies have reported similar results to those reported herein, showing that tea consumption can reduce CHD risk [1112]. In our study, we observed that tea consumption was associated with a reduced risk of CHD in female participants, but not in male participants, in Guangzhou, China.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tea consumption has been shown to be useful for the prevention of many debilitating human diseases. Several published studies have reported similar results to those reported herein, showing that tea consumption can reduce CHD risk [1112]. In our study, we observed that tea consumption was associated with a reduced risk of CHD in female participants, but not in male participants, in Guangzhou, China.…”
Section: Discussionsupporting
confidence: 90%
“…However, another meta-analysis of tea consumption in relation to stroke, myocardial infarction, and all coronary heart disease (CHD) showed that there was an increased risk of CHD and stroke in populations with increased tea consumption [10]. A large prospective study showed that regular green tea consumption was associated with a significantly reduced risk of death from all causes, cardiovascular disease, and cancer among Chinese adults [11]. Unanswered questions from these studies include whether sex, age, type of tea, or the amount of tea consumed can produce these different results.…”
Section: Introductionmentioning
confidence: 99%
“…311 Evidence from China is still limited to male gender, local areas, or a certain disease outcome. 1217 Therefore, the inverse association of tea consumption with ASCVD and all-cause mortality warrants further investigations based on nationwide cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…[97][98][99] These effects translate into a lower risk of developing CHD and major cardiac events, even all-cause mortality. 100,101 The evidence for a favourable CVD profile is based on regular tea consumption (3-5 cups/day) without added sugars, sweeteners or milks and creams (both animal and plant-based), and that should be the proper way to tackle any recommendation on this beverage.…”
Section: Fish and Seafoodmentioning
confidence: 99%